The new essentials cookbook : a modern guide to better cooking (America's Test Kitchen, 2018)
We've made improvements to well-loved dishes by incorporating innovative techniques in recipes such as Butter-Basted Rib-Eye Steak and added modern classics such as Vegetable Bibimbap and Olive Oil-Yogurt Bundt Cake. In this book, you'll find the perfect roast chicken and a killer banana bread but also a Turkish-inspired tomato soup, luscious Chinese braised short ribs, and a set of wholesome grain bowls. A chapter on weeknight dinners offers smart paths to great flavor--from Bucatini with Peas, Kale, and Pancetta that cooks in one pot to a pizza that bakes in a skillet--including plenty of vegetarian options. Other chapters turn up the volume on breakfast and dessert standbys; try the 100 Percent Whole-Wheat Pancakes and Brown Sugar Cookies and you may never go back to the regular versions. We'll also help you pull off your next--or even your first!--dinner party with recipes guaranteed to impress (and to work), such as Braised Lamb Shanks with Bell Peppers and Harissa, Miso-Marinated Salmon, and Roasted Zucchini and Eggplant Lasagna. Most of us--not just newbies--could stand to bone up on certain culinary basics, and our methods may surprise even more experienced cooks, from seeding fresh chiles (we use a measuring spoon) to hulling strawberries (a plastic straw works well). And that's just the tip of the iceberg of what these recipes teach. You'll discover how to "reverse sear" thick pork chops so they turn out juicy all the way through, grind meat in a food processor for the ultimate burger, and shape fresh corn tortillas without a tortilla press or rolling pin.